An assessment of constraints to accurate reporting of cattle mortality in Odi district, North West Province - McCrindle, Cheryl Myra Ethelwyn (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Sciences))--University of Pretoria, 2004.